2004
DOI: 10.1038/sj.bmt.1704760
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of nonmyeloablative allogeneic stem cell transplantation for renal cell carcinoma: The University of Chicago Experience

Abstract: Summary:Nonmyeloablative allogeneic stem cell transplantation (NST) has considerable activity in patients with metastatic renal cell carcinoma (RCC), although there are limited long-term follow-up data. Between February 1999 and May 2003, 18 patients with metastatic RCC underwent 19 matched-sibling NSTs after conditioning with fludarabine and cyclophosphamide with tacrolimus and mycophenolate mofetil as posttransplant immunosuppression. Among the four objective responses, all were partial and have relapsed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…Nevertheless, both interferon alpha and IL-2 are toxic, and the large majority of individuals who receive them derive no benefit. Efforts to develop more sophisticated immunotherapy platforms for this disease, including newer cytokine therapy (Alatrash et al, 2004), vaccine therapy (Uemura et al, 2006;Ernstoff et al, 2007), and nonmyeloablative transplantation (Childs et al, 2000;Artz et al, 2004;Rini et al, 2006), have been reported. Although these approaches have demonstrated tantalising indications of efficacy in a small group of individuals, they have not reached the threshold of therapeutic efficacy or safety.…”
mentioning
confidence: 99%
“…Nevertheless, both interferon alpha and IL-2 are toxic, and the large majority of individuals who receive them derive no benefit. Efforts to develop more sophisticated immunotherapy platforms for this disease, including newer cytokine therapy (Alatrash et al, 2004), vaccine therapy (Uemura et al, 2006;Ernstoff et al, 2007), and nonmyeloablative transplantation (Childs et al, 2000;Artz et al, 2004;Rini et al, 2006), have been reported. Although these approaches have demonstrated tantalising indications of efficacy in a small group of individuals, they have not reached the threshold of therapeutic efficacy or safety.…”
mentioning
confidence: 99%
“…However, the worldwide clinical experience of allogeneic SCT for metastatic RCC is limited, with approximately 200 cases reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15]24 One of the major restrictions of this approach is the requirement that transplant candidates have an HLA-identical related donor. This requirement may limit the use of allogeneic stem cell transplantation to a minority of patients with metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The results of pilot reduced-intensity transplant trials for metastatic RCC are encouraging and show that responses can occur in patients with advanced metastatic disease that has failed to respond to conventional cytokine-based therapy. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15] Unrelated cord blood (UCB) is considered an alternative hematopoietic stem cell source for transplantation, and its use in adult patients with hematologic disorders is increasing. [16][17][18][19][20][21] Thus far, UCB transfer has not been attempted in patients with a solid-organ malignancy such as RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Artz et al ont revu la litté rature et l'expé rience de l'université de Chicago [1]. Ils ont retrouvé 14 é tudes publié es qui ont rapporté 163 patients é valuables : 32 ont pré senté une ré ponse partielle et sept une ré ponse complè te avec un taux de ré ponse globale de l'ordre de 24 %.…”
Section: Carcinome Ré Nalunclassified